Cálculo da porosidade - estimativa do tempo de trânsito da matriz - VALENTE, Adriano Lopes (2018)
Porosity is the fluid volume present in the constitution of sedimentary rocks and can be estimated from the well log data. Density-Neutron crossplot is a classic method for porosity calculation. However in some practical situations the conditions of borehole wall may damage the measurements of density and neutron porosity as wall collapses and formation of thick mudcake. In these situations the sonic log can be used for porosity calculation, once its measurements are not affected by these events. In this case, is mandatory to have a prior knowledge of the matrix transit time. This work (TCC) presents a method to estimate the matrix transit time based in the integration of density-sonic crossplot and matrix density obtained in conventional core analysis. This methodology is presented with synthetic data, according to the petrophysic model and evaluated in real data from a cored borehole in the Namorado field, Campos basin, Brazil.